2020
DOI: 10.1001/jamasurg.2019.5466
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Decompressing Stoma vs Stent as a Bridge to Surgery for Left-Sided Obstructive Colon Cancer

Abstract: Bridge to elective surgery using self-expandable metal stent (SEMS) placement is a debated alternative to emergency resection for patients with left-sided obstructive colon cancer because of oncologic concerns. A decompressing stoma (DS) might be a valid alternative, but relevant studies are scarce.OBJECTIVE To compare DS with SEMS as a bridge to surgery for nonlocally advanced left-sided obstructive colon cancer using propensity score matching. DESIGN, SETTING, AND PARTICIPANTS This national, population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
2
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 38 publications
4
104
2
2
Order By: Relevance
“…Five retrospective studies [ 14 , 22 , 25 , 28 29 ] reported the occurrence of lymphovascular invasion in pathological specimens of colorectal cancer. Veld [ 28 ] subdivided LVI into LI and VI and reported on them separately. The test for overall effect showed that RR was 0.68 (95% CI 0.47, 0.99, P = 0.004) suggested that the rate of LVI positive in the SEMS group was significantly higher than that in the ES group (36.1% versus 22.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Five retrospective studies [ 14 , 22 , 25 , 28 29 ] reported the occurrence of lymphovascular invasion in pathological specimens of colorectal cancer. Veld [ 28 ] subdivided LVI into LI and VI and reported on them separately. The test for overall effect showed that RR was 0.68 (95% CI 0.47, 0.99, P = 0.004) suggested that the rate of LVI positive in the SEMS group was significantly higher than that in the ES group (36.1% versus 22.7%).…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics and quality evaluation of the included studies are shown in Table 1. A total of 22 studies were included in this meta-analysis, including 3 randomized controlled trials(8-10), 1 prospective study (11), and 18 retrospective studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). A total of 1582 patients used SEMS as a bridge to surgery and 1511 patients underwent emergency surgery.…”
Section: Basic Characteristics and Qualitymentioning
confidence: 99%
“…LVI(lymphovascular invasion)( Fig.3): Five retrospective studies (14,22,25,(28)(29) reported the occurrence of lymphovascular invasion in pathological specimens of colorectal cancer. Veld(28) subdivided LVI into LI and VI and reported on them separately.…”
Section: Basic Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations